A Dual Functional Scaffold Tethered with EGFR Antibody Promotes Neural Stem Cell Retention and Neuronal Differentiation for Spinal Cord Injury Repair. Issue 9 (24th February 2017) - Xu, Bai; Zhao, Yannan; Xiao, Zhifeng; Wang, Bin; Liang, Hui; Li, Xing; Fang, Yongxiang; Han, Sufang; Li, Xiaoran; Fan, Caixia; Dai, Jianwu
Abstract : Neural stem cells (NSCs) transplantation is a promising strategy to restore neuronal relays and neurological function of injured spinal cord because of the differentiation potential into functional neurons, but the transplanted NSCs often largely diffuse from the transplanted site and mainly differentiate into glial cells rather than neurons due to the adverse microenviornment after spinal cord injury (SCI). This paper fabricates a dual functional collagen scaffold tethered with a collagen‐binding epidermal growth factor receptor (EGFR) antibody to simultaneously promote NSCs retention and neuronal differentiation by specifically binding to EGFR molecule expressed on NSCs and attenuating EGFR signaling, which is responsible for the inhibition of differentiation of NSCs toward neurons. Compared to unmodified control scaffold, the dual functional scaffold promotes the adhesion and neuronal differentiation of NSCs in vitro. Moreover, the implantation of the dual functional scaffold with exogenous NSCs in rat SCI model can capture and retain NSCs at the injury sites, and promote the neuronal differentiation of the retained NSCs into functional neurons, and finally dedicate to improving motor function of SCI rats, which provides a potential strategy for synchronously promoting stem cell retention and differentiation with biomaterials for SCI repair. Abstract : A dual functional collagen scaffold tethered with an epidermal growth factor receptor antibody is fabricated. The dual functional scaffold can simultaneously promote adhesion and neuronal differentiation of neural stem cells after spinal cord injury (SCI), which provides a potential strategy for synchronously improving stem cell retention and differentiation with biomaterials for SCI repair.